Optimal key based homomorphic encryption for color image security aid of ant lion optimization algorithm - K, Shankar; S.K, Lakshmanaprabu (International Journal of Engineering and Technology, 2018)
The security of digital images is a basic and difficult task on the shared communication channel. Different strategies are utilized to secure the digital image, for example, encryption, steganography and watermarking. These are the techniques for the security of digital image to accomplish security objectives, i.e. secrecy, trustworthiness, and accessibility. In the proposed study, Homomorphic Encryption (HE) with optimal key selection for image security is utilized. Here the histogram equalization is introduced for altering image intensities to improve contrast. The histogram of an image generally speaks to the comparative frequency of occurrence of the different gray levels in the image. To increase the security level inspired Ant Lion Optimization (ALO) is considered, where the fitness function as max entropy the best-encrypted image is characterized as the image with most astounding entropy among adjacent pixels. Analyzing the outcomes from the performed experimental outcomes can accomplish abnormal state and great strength of proposed model compared with other encryption strategies.